Dark solitons in a spinor microcavity-polariton condensate. (October 2016) - Chen, Ting-Wei; Jheng, Shih-Da; Hsieh, Wen-Feng; Cheng, Szu-Cheng
Abstract: Dark solitons of a two-component condensate occurring in nonresonantly-pumped microcavity polaritons (spinor MPCs) with integer vorticities, referred to as integer dark solitons (IDSs), can be excited by a laser beam with tunable polarization and power. We investigate the physical properties of stationary IDSs in a pure spinor MPCs without defects. From the excitations of a IDS, we show that the soliton is stable when the pump power is higher than a critical value. When the pump polarization is in favor of one component, we find that the critical pump power for the stabilization becomes higher. The stable IDS exists below a critical pump polarization. A stable phase diagram of IDSs in terms of the pump condition, i.e., pump polarization and power, is thus obtained. Highlights: The IDS pair developed in a spinor polariton condensate are stable if the pump power is above a critical value. One of the IDS pair behaves as a repulsive potential that stabilizes the dark soliton of the other component. The stability of the IDSs depends on the pump power and pump polarization.